Numerical Investigation on the Effect of the Oxymethylene Ether-3 (OME3) Blending Ratio in Premixed Sooting Ethylene Flames - Schmitz, Robert; Sirignano, Mariano; Hasse, Christian; Ferraro, Federica (Frontiers in Mechanical Engineering, 2021)
Synthetic fuels, especially oxygenated fuels, which can be used as blending components, make it possible to modify the emission properties of conventional fossil fuels. Among oxygenated fuels, one promising candidate is oxymethylene ether-3 (OME3). In this work, the sooting propensity of ethylene (C2H4) blended with OME3 is numerically investigated on a series of laminar burner-stabilized premixed flames with increasing amounts of OME3, from pure ethylene to pure OME3. The numerical analysis is performed using the Conditional Quadrature Method of Moments combined with a detailed physico-chemical soot model. Two different equivalence ratios corresponding to a lightly and a highly sooting flame condition have been investigated. The study examines how different blending ratios of the two fuels affect soot particle formation and a correlation between OME3 blending ratio and corresponding soot reduction is established. The soot precursor species in the gas-phase are analyzed along with the soot volume fraction of small nanoparticles and large aggregates. Furthermore, the influence of the OME3 blending on the particle size distribution is studied applying the entropy maximization concept. The effect of increasing amounts of OME3 is found to be different for soot nanoparticles and larger aggregates. While OME3 blending significantly reduces the amount of larger aggregates, only large amounts of OME3, close to pure OME3, lead to a considerable suppression of nanoparticles formed throughout the flame. A linear correlation is identified between the OME3 content in the fuel and the reduction in the soot volume fraction of larger aggregates, while smaller blending ratios may lead to an increased number of nanoparticles for some positions in the flame for the richer flame condition.